Choosing optimal omnichannel coupon redeeming options in multiple channel settings - Adam Vrechopoulos; Chris Lazaris; Stavros Theodoratos (Administrative Sciences, 2022)
This article examines omnichannel redemption options when issuing digital coupons over social media. It investigates which channels or combinations of them provide optimal performance in terms of service-quality perception, customer satisfaction, and revenue. For that purpose, it compares three omnichannel redeeming options employing a between-participant quasi-experimental design that utilizes the primary data of a sporting goods retailer in Greece and a questionnaire as a data-collection instrument to investigate cause and effect relationships. Those three omnichannel redeeming options are analyzed in two pairwise comparisons: (a) multichannel (both online and offline) vs. offline-only (physical store), and (b) multichannel (both online and offline) vs. online-only (online store). Results reveal that while perceived service quality is essential to improve customer satisfaction, especially if satisfying the need for interaction with service employees, revenue performance depends only on the availability of multiple redemption options. Theoretical, practical, and research implications are thoroughly discussed at the end.
Keywords: 350; coupons; customer satisfaction; omnichannel retailing; perceived service quality; store revenues